A New Technology of Recycling Mica Plata Leftover Materials - X. W. Zhang (International Mineral Processing Congress, 2014)
Mica plate is broadly used in electric industry, production of man-made mica paper plate is in-creasing. The problem coming with is that large quantities of leftover materials unable to be re-cycled are produced during cutting and molding of mica plate productions. The leftover materials are always abandoned as crabs, which not only pollute the environment but also waste our resources. The study intends to find a new measure to decompose and to reuse the mica plate leftover materials so as to create a new production process of mica plate, which is clean and does not produce crabs.